Founder events and pre-glacial divergences shape the genetic structure of European Collembola species. Issue 1 (December 2016) - von Saltzwedel, Helge; Scheu, Stefan; Schaefer, Ina
Abstract Background Climate oscillations in the Cenozoic reduced species richness and genetic diversity of terrestrial and aquatic animals and plants in central and northern Europe. The most abundant arthropods in temperate soils are Collembola that live in almost any soil-related habitat. Extant species show little morphological variation to Eocene fossils, suggesting persistence of species in stable habitats for millions of years. Collembola are able to evade adverse climatic conditions by moving into deeper soil layers and are tolerant to frost and draught. If these adaptations sufficed for surviving glacial periods remains open and needs to be investigated in a phylogeographic context, i.e. investigating spatial structure on molecular level. We investigated the molecular variation of three common species of Collembola at a pan-European scale to identify glacial refuges and post-glacial colonization patterns with three genetic markers. Results All genes revealed remarkable genetic structure between but not within populations, suggesting density dependent processes for establishment of populations (founder-takes-all principle), which is common for European animals and plants. In contrast to the post-glacial recolonization patterns of many aboveground organisms, divergence times of most geographic lineages indicate preservation of genetic structure since the Miocene. Conclusions Collembola survived severe climatic changes including those during Quatenary glaciation and kept high genetic variance across Europe. Likely the buffering of temperature oscilliations in soil and the ability to evade adverse climatic conditions due to cold-tolerance and horizontal migration enabled Collembola to evade strong selective pressure of abiotic forces.